Bioestimulante a base de compuesto rumial sobre la productividad en el cultivo de pimiento (capsicum annum l). - Cedeño Zambrano, Roxy Bernal (2013)
The present investigation was carried out in the dry time of the year 2011 in the ecological area of the polytechnic campus of the ESPAM MFL with the purpose of studying a bioestimulante (biol) with the help of compound rumial about the productivity of the pepper cultivation (Capsicum annum L); the factors in study were, dilution percentage (10%,20% and 30%) and application frequency (8, 15 and 22 days). a Design of Complete Blocks was used at random to prepare the distribution of the ten treatments, included the absolute witness, and the three reply. In block the plántula height was controlled to the moment of the transplant. In the phase experimental pre it was analyzed chemistry and microbiológicamente to the compound rumial and biol; established the rehearsal the variable answers were directed to the vegetative and productive development of cultivating that they were evaluated statistically; with the yield he/she was carried out an economic analysis by means of the methodology of the CYMMYT. In the analyses of the compound rumial he/she was 11.46 protein% and 30.05 fiber% that which served as base for the fermentation anaeróbica and obtaining of the biol free of polluting agents and with very low levels of macroelementos; in microelementos it stood out the iron and manganese respectively with 89 and 25 ppm. The concentration of these nutritious elements didn't impact since on the vegetative and productive development of the pepper H. Quetzal all the variants they went statistically similar to the witness that didn't receive the biol. From the economic point of view the best option is to apply a dilution of 10 biol% every 22 days.